2011
DOI: 10.1073/pnas.1011560108
|View full text |Cite
|
Sign up to set email alerts
|

Validation of isoleucine utilization targets in Plasmodium falciparum

Abstract: Intraerythrocytic malaria parasites can obtain nearly their entire amino acid requirement by degrading host cell hemoglobin. The sole exception is isoleucine, which is not present in adult human hemoglobin and must be obtained exogenously. We evaluated two compounds for their potential to interfere with isoleucine utilization. Mupirocin, a clinically used antibacterial, kills Plasmodium falciparum parasites at nanomolar concentrations. Thiaisoleucine, an isoleucine analog, also has anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
147
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 24 publications
1
147
0
Order By: Relevance
“…Their similar IC 50 values at both 48 and 96 h suggest that these compounds inhibit cytosolic ARS. Natural product ARS inhibitors were also screened for antimalarial activity (Table 1 (17) and consistent with its high selectivity toward bacterial-type enzymes (33,34), such as the apicoplast-targeted isoleucyl-tRNA synthetase (IleRS-2). This phenomenon was observed even when mupirocin was removed from the culture after the first cycle of incubation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their similar IC 50 values at both 48 and 96 h suggest that these compounds inhibit cytosolic ARS. Natural product ARS inhibitors were also screened for antimalarial activity (Table 1 (17) and consistent with its high selectivity toward bacterial-type enzymes (33,34), such as the apicoplast-targeted isoleucyl-tRNA synthetase (IleRS-2). This phenomenon was observed even when mupirocin was removed from the culture after the first cycle of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Although underexploited for many years, recent work has shown that plasmodial ARS are not only druggable enzymes (17,18) but also that selective inhibition of these enzymes versus their human homologs is feasible (16). In this work, we evaluated and tested a series of known ARS inhibitors on P. falciparum cell cultures and explored their ability to inhibit parasite replication in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, mupirocin was also shown to inhibit blood stage of P. falciparum in the nanomolar range 8 through the inhibition of apicoplastic IleRS. However, mupirocin failed to protect mice from systemic P. berghei infection, probably due to its in vivo instability and its high binding to serum.…”
mentioning
confidence: 99%